Air quality trends in an industrialised area of SW Spain. (10th June 2018) - Sánchez de la Campa, Ana M.; Sánchez-Rodas, Daniel; Alsioufi, Louay; Alastuey, Andrés; Querol, Xavier; de la Rosa, Jesús D.
Abstract: Copper smelters represent a major anthropogenic source of SO2 and sulphide-related elements into particulate matter, affecting the air quality of the surrounding areas. The implementation of measures to reduce the emission of gaseous contaminants and particles in industrial processes is a major issue, which aims to establish technological progress for cleaner production. In this sense, a long-range study covering the period 2001–2015 has been performed in the SW Spain, where one of the largest Cu-smelters in Europe is located. Trends of PM10 and PM2.5 levels and geochemical patterns were studied considering the following periods: prior (2001–2008), during (2009–2013) and after (2014–2015) the implementation of emission abatement technology (wet electrofilters, bag filters and lime injection) by this large industrial facility. The results evidenced relatively high concentrations of sulphide-related elements (annual mean of 6.1, 1.7, 0.7, 2.2, 2.0, 21.0 and 1.0 ng m −3 for As, Se, Cd, Sn, Sb, Pb and Bi, respectively) during 2001–2008. A reduction of 50% was observed for the last period (2.8, 0.5, 0.2, 1.6, 1.1, 6.7 an d 0.3 ng m −3 for the same elements, respectively) in PM10 . A similar trend was observed for PM2.5 samples. However, the number of episodes of SO2 has not changed along the studied period (average 8 days/month), although the SO2 concentration during the pollution episodes has markedly diminished from maximum peak concentrations of 350 μg m −3 to 170 μg m −3 . A high arsenic concentration is the main geochemical anomaly found in PM, reaching annual mean concentrations up to 10.4 ng m −3 in 2005 above the annual EU target value (6 ng m −3 ) in PM10, decreasing down to 2.7 and 2.9 ng m −3 in 2014 and 2015, respectively. However, sporadically high episodic levels are still recorded (e.g. 26.8 ng m −3 in 2014 and 14.9 ng m −3 in 2015). Graphical abstract: Image 1 Highlights: Air quality of an industrialized area (SW Spain) has been studied during 2001–2015. Geochemical anomalies due to Cu-smelter emission were found in PM10 and PM2.5 . Emission abatement technology at the Cu-smelter has been implemented in 2009–2013. 50% decrease of sulphide-related elements (As, Se, Sn, Cd, Pb and Bi) was observed. As speciation showed that As(V) (>90%) was the main specie compared to As(III).